Processes of Heat and Mass Transfer During Grain Mass Storage in Metal Silos of Large Capacity - Kechkin , Ivan; Ermolaev, Vladimir; Belyaeva, Marina; Tarakanova, Valentina; Gurkovskaya, Elena; Buzetti, Konstantin (KnE Life Sciences, 2021)
This study showed that there were some changes in the temperature and humidity parameters of wheat grains during the storage year. The grain moisture content in both the near-wall and central parts of the metal silo largely did not change, remaining at a level of 10-11%. Moisture values were recorded monthly, and grain temperature was recorded in accordance with seasonal changes, thus, the range of temperature changes was from 20 to 32°С at a minimum outdoor temperature of 5°С. The moisture content of the grain in the surface layer increased by 0.4-1.2% and the final moisture content of the grain was 11.6%. Experiments on grain temperature and humidity changes with active ventilation in large-capacity metal silos have shown that the rate of change (decrease) in temperature depends on the specific air flow rate, and the difference in air and grain temperature. Experimental storage showed that a grain with the moisture content up to 13.6% can be stored for up to nine months without deterioration in quality. A longer shelf life is possible for wheat grains with a moisture content of up to 12%. This article pays special attention to the processes occurring in the under-roof space of large-capacity metal silos and suggests methods for solving this problem. Keywords: long-term storage, active ventilation, metal silos, heat and mass transfer processes